Change detection in very high resolution imagery and vector data applied to the monitoring of geographical conditions. Issue 4 (19th September 2016) - Zhao, Zhenzhen; Lin, Aiwen; Yan, Qin; Feng, Jiandi
Abstract : Purpose: Geographical conditions monitoring (GCM) has elicited significant concerns from the Chinese Government and is closely related to the "Digital China" program. This research aims to focus on object-based change detection (OBCD) methods integrating very-high-resolution (VHR) imagery and vector data for GCM. Design/methodology/approach: The main content of this paper is as follows: a multi-resolution segmentation (MRS) algorithm is proposed for obtaining homogeneous and contiguous image objects in two phases; a post-classification comparison (PCC) method based on the nearest neighbor algorithm and an image-object analysis (IOA) technique based on a differential entropy algorithm are used to improve the accuracy of the change detection; and a vector object-based accuracy assessment method is proposed. Findings: Results show that image objects obtained using the MRS algorithm attain the objectives of the "same spectrum within classes" and "different spectrum among classes". Moreover, the two OBCD methods can detect over 85 per cent of the changed regions. The PCC strategy can obtain the categories of image objects with a high degree of precision. The IOA technique is easy to use and largely automated. Originality/value: On the basis of the VHR satellite imagery and vector data, the above methods can effectively and accurately provide technical support for GCM implementation.